MEDICINAL PROPERTIES OF SPECIES OF THE KOVRAK (FERULA L.) GROUP - Berdikulova Nargiza Yusufjon qizi; Khushnazarova N.D. (TADQIQOTLAR.UZ, 2023)
Central Asia, including the territory of our Republic, is a land rich in medicinal plants. Among the useful plants, representatives of the Apiaceae L. family occupy a special place. Among this family, Ferula L. has the largest number of species (180- 200), more than 110 of which are found in Central Asia and Kazakhstan, and 44 in Uzbekistan. Species of this group are essential oil, fodder, honey, medicinal, starchy, aromatic, nutritious and technical plants.